Amenable deaths among adults with intellectual and developmental disabilities including Down syndrome: An Ontario population‐based cohort study. Issue 1 (15th November 2022) - Lin, Elizabeth; Lunsky, Yona; Chung, Hannah; Durbin, Anna; Volpe, Tiziana; Dobranowski, Kristin; Benadict, Mary Benisha; Balogh, Robert
Abstract: Background: Rates of death and avoidable deaths are reportedly higher among people with intellectual and developmental disabilities. This study contributes to our understanding of how mortality and intellectual and development disabilities are associated. Method: General population and intellectual and developmental disabilities adult cohorts were defined using linked administrative data. All‐cause and amenable deaths between 2010 and 2015 were reported for these cohorts and subcohorts with and without Down syndrome. Cox proportional hazards models evaluated the impact of potential contributors to amenable deaths. Results: Adults with intellectual and developmental disabilities had higher all‐cause (6.1 vs. 1.6%) and amenable death percentages (21.4 vs. 14.1%) than general population comparators. Within intellectual and developmental disabilities, those with Down syndrome had higher all‐cause (12.0 vs. 6.0%) but lower amenable death percentages (19.2 vs. 21.8%) than those without. Conclusions: Results suggest that interventions to reduce amenable deaths target provider‐care‐recipient interactions and coordination across care and support sectors.